Digging process in NGC 6951: the molecular disc bumped by the jet. Issue 1 (27th January 2016) - May, D.; Steiner, J. E.; Ricci, T. V.; Menezes, R. B.; Andrade, I. S.
Abstract: We present a study of the central 200 pc of the galaxy NGC 6951, SAB(rs)bc, an active twin of the Milky Way, at a distance of 24 Mpc. Its nucleus has been observed in the optical with the Integral Field Unit of the Gemini Multi-Object Spectrograph, showing an outflow, and with the HST /ACS, revealing two extended structures with similar orientation, suggesting the presence of a collimating and/or obscuring structure. In order to ascertain this hypothesis, adaptive optics assisted NIR integral field spectroscopic observations were obtained with the Near-Infrared Integral Field Spectrograph in the Gemini North telescope. We detected a compact structure of H2 molecular gas, interpreted as a nearly edge-on disc with diameter of ∼47 pc, PA = 124° and velocity range from −40 to +40 km s −1 . This disc is misaligned by 32° with respect to the radio jet and the ionization cones seen in the optical. There are two regions of turbulent gas, with position angles similar to the jet/cones, seen both in molecular and ionized phases; these regions are connected to the edges of the molecular disc and coincide with a high ratio of [N ii ]/H α = 5, suggesting that these regions are shock excited, partially ionized or both. We explain these structures as a consequence of a 'digging process' that the jet inflicts on the disc, ejecting the molecular gas towards the ionization cones. The dynamical mass within 17 pc is estimated as 6.3 × 10 6  M⊙ . This is an interesting case of an object presenting evidence of a connected feeding-feedback structure.